Expansion sheet for thermal runaway management of electric vehicle battery
By using inorganic expansion sheets with a thickness less than or equal to 1mm as battery cell spacers, and utilizing a combination of alkali metal silicate-based adhesives and microporous additives, the deficiencies in battery thermal runaway management in the existing technology are solved and achieved. Good thermal conductivity under normal operating conditions and an effective low thermal conductivity barrier in the event of thermal runaway ensure battery safety and fire resistance.
Patent Information
- Application Number
- CN202380046256.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to effectively manage the thermal runaway of electric vehicle (EV) lithium-ion batteries, especially in the event of thermal runaway, to prevent thermal runaway from adjacent battery cells, and the existing spacers are insufficient in thermal conductivity under normal working conditions. The thermal conductivity is too high when out of control, which increases the risk of thermal runaway.
Inorganic expansion sheets with a thickness less than or equal to 1mm are used as spacers between battery cells to form mechanically strong inorganic carbon with good thermal insulation and dielectric strength. A combination of pore additives ensures a low thermal conductivity barrier in the event of thermal runaway.
Provides relatively good thermal conductivity under normal operating conditions, reducing the risk of thermal runaway of battery cells; in the event of thermal runaway, the expansion sheet rapidly expands to form low thermal conductivity carbon, effectively preventing thermal runaway of adjacent battery cells and providing excellent Mechanical strength and dielectric isolation to control fire within the module/battery pack.
Smart Images

Figure BDA0005180429190000111 
Figure BDA0005180429190000112 
Figure BDA0005180429190000151
Abstract
Description
Technical Field
[0001] The present invention relates to an expansion sheet for thermal runaway management of electric vehicle (EV) batteries and a method for making the expansion sheet. In particular, passive thermal runaway management and fire protection of EV batteries can be provided. One or more expansion sheets can be used for various levels of EV batteries, such as for spacing between batteries, and as a lining of the inner wall of a module or battery pack. Background Art
[0002] The global electric vehicle (EV) market has seen tremendous growth over the past decade, reaching $163.01 billion in 2020 and is expected to reach $823.75 billion by 2030. Factors such as the increasing involvement of countries in addressing climate change, commitments to achieve net zero carbon emissions, and rising fuel prices have been the driving forces behind these growths. However, despite the popularity of EVs, fire safety issues with the lithium-ion batteries (LiBs) they use have been a significant barrier to their wider adoption. Several incidents of EV battery-related fires have been reported, with Hyundai Motor and General Motors having to recall more than 100,000 vehicles each in 2020 due to such incidents. This clearly demonstrates the importance of improved fire protection measures to mitigate these issues.
[0003] like Figure 1 As shown, the LiB of an EV consists of three levels, namely: battery cells (104), modules (102) and battery packs (100). A series of battery cells (104) constitute a module (102), and a group of modules (102) constitute a battery pack (100). The maximum operating temperature range of LiB is generally 150°C or lower. If the temperature of a battery cell exceeds this operating temperature limit, an uncontrollable chain of accelerated exothermic reactions may be triggered, causing the temperature to rise to 900°C and releasing a large amount of smoke, shrapnel and other particles in an explosive manner. This process is called "thermal runaway". If not controlled, the high temperature and high pressure generated by the thermal runaway of one battery cell may trigger the thermal runaway of the next battery cell. Subsequently, a thermal runaway "domino effect" may occur in a very short period of time, whereby all battery cells in the module and even the entire battery pack will experience thermal runaway, posing a huge explosion and fire hazard to the EV.
[0004] Typically, two types of thermal runaway management systems are used to prevent multiple battery cells from thermal runaway. The first ensures that the temperature of each battery cell does not exceed the maximum operating temperature. The second ensures that if one battery cell experiences thermal runaway, adjacent battery cells are prevented from thermal runaway.
[0005] The first type of thermal runaway management system includes active monitoring systems, where sensors are used to detect in real time whether temperature or voltage has reached unsafe levels, such as described in US Pat. No. 7,433,794 B1. However, such systems may not be economically feasible.
[0006] The first type of thermal runaway management system also includes passive systems, such as fluid cooling by the principle of heat exchange, in which the module is immersed in a circulating cooling liquid (i.e., refrigerant) or air, as described in US patent application 20200112073A1 or Japanese patent JP6331017B2, respectively.
[0007] In addition, a heat sink, a high thermal conductivity, high emissivity sheet, can be used as a spacer between battery cells to evenly diffuse the heat between battery cells within the module and release the heat to the surroundings by radiation, thereby reducing the risk of thermal runaway in any battery cell. For example, Korean patent KR200479471Y1 uses a compressed sheet made of exfoliated graphite particles or a graphitized polyimide sheet with an in-plane thermal conductivity of 300W / mK. However, if a battery cell does experience thermal runaway, such a heat sink may increase the likelihood of thermal runaway in all battery cells due to its high thermal conductivity. In addition, such a heat sink may not have the dielectric strength to prevent voltage surges from being transferred from one battery cell to an adjacent battery cell, thereby triggering thermal runaway.
[0008] Finally, sheets made of phase change materials can also be applied between battery cells to reduce the heat generated by any battery cell, thereby reducing the risk of any battery cell experiencing thermal runaway. Such an example is described in Chinese patent document CN105742755B, in which a paraffin expanded graphite composite is used as a phase change layer. The disadvantage of using such a phase change sheet is that the amount of heat that such a sheet can absorb is limited, that is, once all modules have undergone a phase change, the sheet cannot absorb more heat. In addition, such a phase change sheet, especially when using a flammable phase change material such as paraffin, may accelerate the thermal runaway of an adjacent battery cell if one of the battery cells experiences thermal runaway. As shown in Chinese patent document CN107887671B, a combination of a phase change sheet and a heat sink has also been adopted as a composite laminate, but the disadvantages of the phase change sheet also exist.
[0009] The second type of thermal runaway management involves using heat-resistant insulating foams, sheets or expansion sheets or a combination thereof as spacers between battery cells as a means of preventing adjacent battery cells from experiencing thermal runaway when one battery cell experiences thermal runaway. Foam is often chosen as a spacer for this technology due to its low thermal conductivity. However, the disadvantage of foam is that its working principle is contrary to the heat dissipation principle during normal battery operation, that is, during normal battery operation, if the battery heats up, the foam will prevent the heat from diffusing, thereby increasing the risk of thermal runaway of the battery.
[0010] An example of a foam spacer is described in International Patent Publication No. WO2021019495A1, which uses a flexible flame retardant polymer foam in combination with a water-based flame retardant silicone elastomer and an inorganic fiber layer. It is impossible to maintain the integrity of such a polymer foam during thermal runaway, so the polymer intumescent coating of the patent document is required. However, the expanded fluffy carbonaceous char produced by the expansion of the intumescent coating has poor dielectric strength and poor ability to withstand the high pressure of smoke and shrapnel.
[0011] Another example of a foam is the flexible silica aerogel sheet used in Chinese patent document CN108862286B. Although it is fireproof and heat resistant, its ability to prevent the transfer of high-pressure smoke and shrapnel is questionable due to its porosity and lack of mechanical strength.
[0012] Canadian patent CA3008606C describes a composite laminate in which a thermally conductive polymer sheet with a low melting point is laminated with an expansion layer. During normal operation, heat diffusion reduces the risk of thermal runaway of each battery cell, and in the event of thermal runaway of one battery cell, the thermally conductive polymer layer in the adjacent spacer easily melts, causing the expansion layer to expand and form a low thermal conductivity carbonaceous char between the participating battery cell and the adjacent battery cell. However, the dielectric strength of the resulting carbonaceous char and the mechanical strength to resist smoke and shrapnel pressure are issues of concern.
[0013] In JP2013528911A, a heat absorbing fireproof coating such as gypsum is used to coat the array of battery cells in the module and part or the entire exterior of the individual battery cells. The char produced during a thermal runaway event is expected to have higher dielectric and mechanical strength than carbonaceous char, but the mechanical strength may still be insufficient to withstand the pressure generated by smoke and shrapnel. In addition, the thermal conductivity of the char produced is expected to be significantly higher than that of carbonaceous char. Summary of the invention
[0014] Overview
[0015] According to an example of the present disclosure, there is provided an expansion sheet as claimed in the independent claim. Some optional features are defined in the dependent claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 (Prior Art) is a schematic diagram of a typical 3-stage battery in an electric vehicle. DETAILED DESCRIPTION
[0017] Detailed description
[0018] Examples of the present disclosure include an expansion sheet having a thickness of less than 2 mm that is capable of expanding to produce a mechanically strong inorganic char with good thermal insulation and dielectric strength. "Char" refers to a material that has been charred or burned. The expansion sheet may or may not be made of an inorganic material. Depending on the application, the expansion sheet may be as thin as 1 mm or less, or thicker than 1 mm. One or more expansion sheets may be used as spacers in electric vehicle (EV) batteries. These spacers may be located between battery cells and in the inner wall lining of the module and the battery pack housing. This can prevent thermal runaway of multiple battery cells and control the fire within the module / battery pack when thermal runaway occurs. Multiple expansion sheets can be stacked layer by layer to form one or more laminates with a thickness that meets the application requirements. One or more laminates may be laminated or coated in the walls of battery cells, modules and / or housings of EV batteries.
[0019] In this disclosure, an electric vehicle (EV) refers to a vehicle that uses one or more electric motors for propulsion and is usually powered by batteries. EVs include, but are not limited to, road and rail vehicles (such as electric scooters, electric bicycles, electric cars, space exploration vehicles, etc.), surface and underwater vessels, electric aircraft (such as manned / unmanned aircraft, drones, etc.) and electric spacecraft.
[0020] Since space constraints are a key factor for EV battery manufacturers, thin spacers with thicknesses as low as 2 mm or less are highly desirable. Various approaches have been used to manage thermal runaway in EV lithium batteries (LiBs), but there is still a lack of a thin battery cell-cell spacer, module liner, and battery pack liner that can provide relatively good thermal conductivity under normal operating conditions, very low thermal conductivity when one or more battery cells experience thermal runaway, and excellent mechanical strength and dielectric resistance. Examples of the present disclosure provide one or more expansion sheets that address these problems. Specifically, the present invention provides an expansion sheet having a thickness of less than or equal to 1 mm.
[0021] The advantage of intumescent coatings or sheets over using foams is that they have higher thermal conductivity before the battery cells thermally run away (i.e. under normal operating conditions). They allow the heat to diffuse, and when the first battery cell thermally runs away, they expand to form a low thermal conductivity char to prevent thermal runaway of adjacent battery cells.
[0022] In one example of the present disclosure, an inorganic expansion sheet is provided, and in its most basic form, it comprises a nonwoven inorganic fiber mat impregnated with a water-based and alkali metal silicate-based solution. In this embodiment, the impregnation solution comprises an alkali metal silicate-based binder, a porous thermal insulation additive, a carbon strength additive, one or more surfactants, water, one or more hardeners, and other additives such as organic additives. The expansion sheet has an alkali metal silicate-based coating containing these additives after drying and / or curing.
[0023] The alkali metal silicate-based binder can be lithium silicate, potassium silicate and sodium silicate or a mixture thereof. Potassium silicate and / or sodium silicate are preferred because lithium silicate is more expensive. Such alkali metal silicates can expand at high temperatures to produce inorganic expanded carbon. Sodium silicate is not as stable as potassium silicate and requires a lower temperature for expansion, so it can be activated earlier when a battery cell experiences thermal runaway. Therefore, between potassium silicate and sodium silicate, sodium silicate is preferred if earlier activation is required.
[0024] The "silicon dioxide: alkali metal oxide" molar ratio of the alkali metal silicate binder determines properties such as the curing rate, the flexibility of the cured sheet, and the degree of expansion and mechanical robustness of the charcoal when the cured sheet is exposed to high temperatures. "Cured sheet" refers to the inorganic expanded sheet after preparation of the above example. A low ratio will result in high expansion, low mechanical robustness of the charcoal, high flexibility of the cured sheet and slow curing rate, while the opposite is true for higher ratios. Taking into account the best compromise between these factors, the molar ratio is preferably in the range of 2.5 to 4, more preferably in the range of 3 to 3.3. The alkali metal silicate content should be between 60 and 95 weight percent (wt%) of the expanded sheet, and more preferably between 75wt% and 85wt% of the expanded sheet to obtain a good balance between expansion capacity and mechanical robustness of the charcoal.
[0025] Micropore and / or mesopore and / or nanopore additive are added to the expansion sheet of above-mentioned example, as can form the reagent of the charcoal with the high pore volume fraction of micropore and / or mesopore and / or nanopore network that has close network and represents uniform distribution.Micropore and / or mesopore and / or nanopore additive are heat-insulating additive.According to the miscibility of heat-insulating additive in impregnation solution (i.e. water-based and alkali metal silicate-based solution), its addition can be 0.5wt% to 10wt% of expansion sheet.Micropore and / or mesopore and / or nanopore additive can make expansion sheet densification.In addition, micropore and / or mesopore and / or nanopore additive can be silicon dioxide and / or silicate in nature.
[0026] Examples of microporous and / or mesoporous and / or nanoporous additives include, but are not limited to, hollow microglass spheres, fumed silica, hollow microspheres, and aerogel particles. It has been observed that the addition of aerogel particles with hydrophobic surface groups has shown good performance in forming microporous and / or mesoporous carbons with a dense network and a high pore volume fraction. More preferably, a particle size of 10 μm to 60 μm, a pore size of 5 nm to 50 nm, a porosity of >90%, and a bulk density of 0.02 g / cm 3 To 0.1g / cm 3 , surface area is 500m 2 / g to 900m 2 / g of aerogel particles. The aerogel content should be 0.5wt% to 10wt% of the expanded sheet, preferably 1wt% to 5wt% of the expanded sheet. Above the recommended range, dispersibility will become a problem, while below this range, the barrier improvement of the carbon is not significant enough.
[0027] In the absence of added microporous and / or mesoporous and / or nanoporous additives, the expanded carbon produced from the expanded sheet with the alkali metal silicate based binder alone can be a loosely connected network with a large pore size distribution.
[0028] For comparison, (a) the carbon sample of the alkali metal silicate-based binder alone was magnified 100 times and 1000 times, and (b) the carbon sample of the expanded sheet with the alkali metal silicate-based binder and the addition of 1wt% of the above-mentioned aerogel particles was magnified 100 times, 1000 times and 5000 times. The carbon of (a) shows a loosely connected network with a large pore size distribution. The pore size is not uniform, and the walls forming the pores appear fragile and brittle. In contrast, the carbon of (b) shows a significantly denser network with a significantly high pore volume fraction, representing a uniformly distributed micropore and / or mesopore and / or nanopore network. At a magnification of 100 times, for the carbon of (a), almost every pore is visible and appears large, but for the carbon of (b), few pores have the same large-sized appearance, and most of the pores are invisible. Even at a higher magnification of 5000 times, the pore volume of the carbon of (b) still appears very high and the pore distribution still appears uniformly distributed. At 1000 times magnification, only very few pore walls can be seen for the carbon of (a). However, even at 5000 times magnification, the pores and their walls of the carbon of (b) are almost invisible. From this comparison, it can be clearly seen that the carbon obtained by the example of the alkali metal-silicate-aerogel combination has excellent properties in terms of thermal insulation and carbon strength. The carbon has such a dense network, high pore volume and distribution. It should be noted that such microporous and / or mesoporous and / or nanoporous additives do not cause or affect the degree or effect of expansion, which is mainly caused by the degradation of the alkali metal silicate based binder. Having such additives enhances the strength of the carbon and its ability to reduce the heat flow transfer rate.
[0029] Optionally, the expansion sheet of the above example may include a carbon strength enhancing additive to further improve the mechanical robustness, barrier properties and flame retardant properties of the carbon. Carbon strength enhancing additives include one or more metal salts, including but not limited to, individual metal oxides such as magnesium oxide, aluminum oxide, calcium oxide and zinc oxide, metal hydroxides such as aluminum trihydrate and magnesium dihydroxide, metal carbonates such as calcium carbonate and zinc carbonate, metal silicates such as mica and talc, and metal powders such as iron, zinc and aluminum, or any combination thereof. The above metal hydroxides and carbonates can also act as endothermic additives to provide additional fire protection by endothermic cooling at higher temperatures (i.e., above 200°C). The total loading level of such carbon strength enhancing additives added should be between 1wt% and 10wt% of the expansion sheet, or preferably between 3wt% and 8wt% of the expansion sheet to obtain the best balance between the expansion ability and mechanical robustness of the carbon.
[0030] Optionally, 1 wt% to 10 wt% of an opacifier such as iron oxide, silicon carbide and titanium dioxide may be added to the intumescent sheet. The opacifier provides high temperature insulation and acts to reflect, thereby reducing heat transfer by radiation at high temperatures.
[0031] Optionally, a surfactant can be added to the impregnation solution (i.e., water-based and alkali metal silicate-based solution) for making the expansion sheet of the above-mentioned example. Adding a surfactant improves the dispersibility of the additive and the ability of the impregnation solution to spread and wet the nonwoven fiber mat. Due to the alkalinity of the impregnation solution, the selection of the surfactant should make it stable in the range of pH 2 to 12. Preferably, the surfactant or its mixture is selected from the group consisting of amine oxide, alkyl carbohydrate ester, alkoxylated polysiloxane and polyalkyl acrylate. The surfactant loading level can be 0.05wt% to 2wt% of the impregnation solution, and is preferably 0.2wt% to 0.5wt% of the impregnation solution, because a higher surfactant loading level may cause adverse changes in flame retardant properties, and a lower loading level may not improve uniformity and the ability to fully wet the nonwoven fabric.
[0032] Optionally, a hardener can be added to the impregnation solution (i.e., water-based and alkali metal silicate-based solution) used in the process of manufacturing the expansion sheet of the above-mentioned example. Adding a hardener improves the drying and curing time of the impregnated non-woven fiber mat. Such hardeners are conducive to the large-scale production of expansion sheets, especially for conveyor-type continuous production lines, and can be roughly divided into acid-based or alkaline hardeners. Acid-based hardeners include, but are not limited to, hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, aluminum phosphate and sodium fluorosilicate, and the most commonly used alkaline hardener is potassium methyl silicate. Acids in the form of solid powders with slow dissolving properties are preferred to prevent coagulation during the working time (i.e., during the impregnation of the non-woven fiber mat), and therefore, sodium fluorosilicate is preferably selected in the acidic hardener. Potassium methyl silicate is preferred in the alkaline hardener. In addition, the hardener improves the water resistance of the prepared cured impregnated expansion sheet, thereby reducing the risk of damage during storage. The amount of hardener added depends specifically on the manufacturing method and requirements. However, high load levels tend to significantly reduce flexibility, so such hardeners are preferably less than 10wt% of the expansion sheet.
[0033] Optionally, organic additives can be added to enhance the flexibility and water resistance of the expansion sheet of the above-mentioned example. To this end, a variety of organic additives and combinations thereof can be added. For example, they can be in the form of latex, emulsion, suspension, solution or solid powder. Organic additives may include, but are not limited to, thermoplastic or thermosetting polymers, such as polymethyl methacrylate, polyacrylic acid, polyvinyl alcohol, polyvinyl acetate, polyvinyl acrylate, polyvinyl pyrrolidone, poly (ethyl-vinyl acetate), styrene-butadiene rubber, polyethylene glycol, polyurethane, polyester and epoxy resin, and organic molecules or macromolecules, such as ethylene glycol, pentaerythritol, glycerol, starch, mannitol and carboxymethyl cellulose. Water-based organic additives are preferred because they can be stably added to the impregnation solution without forming aggregation during work. Among them, when adding appropriate levels, glycerol and polyvinyl alcohol especially show good miscibility and improvement in flexibility, and will not affect flame retardant properties, so they are preferred choices. Adding high levels of such organic additives may cause flame retardant properties to be significantly reduced, so it is preferred that the addition amount of such organic additives should be less than 10wt% of the expansion sheet.
[0034] The inorganic nonwoven fiber mat of the expansion sheet of the above example has two important functions. It improves the flexibility of the expansion sheet and ensures that the char formed during the thermal runaway event of the EV battery has higher mechanical robustness. Glass fiber-based nonwoven fiber mats are preferred. It is composed of the type, diameter and length of the fibers used, the type and amount of the binder used, and the area density (i.e. g / m 2 ) definition. Suitable choices for non-woven glass fiber mats or fabrics for producing expansion sheets include types E, S, C, R, T and A, with types E and S being preferred choices. The diameter and length of the fibers may be between 8μm and 18μm and 10mm and 75mm, respectively, and preferably between 10μm and 15μm and 15mm and 60mm. The type of adhesive selected should remain stable in the alkaline environment inside the EV battery and in any coolant to which the expansion sheet will come into contact. The amount of adhesive should be sufficient to impart flexibility, but not too high as this will negatively affect flame retardancy. For example, a polymer adhesive may be used. Specifically, an acrylic resin may be selected as the binder, the content of the binder being 5wt% to 20wt% of the non-woven fiber mat, preferably 8wt% to 15wt% of the non-woven fiber mat. The area density may be less than 400g / m 2 , and preferably at 30g / m 2 Up to 280g / m 2 The nonwoven fiber mat may account for 5 wt % to 20 wt % of the intumescent sheet composition, preferably 8 wt % to 16 wt % of the intumescent sheet.
[0035] To produce the intumescent sheet of the above example, a nonwoven fiber mat is first laminated on a non-stick polymer sheet and impregnated with an alkali metal silicate-based aqueous solution (also referred to as "impregnation solution" in the present disclosure), the solution comprising, for example, in a 100 wt % alkali metal silicate-based solution,
[0036] a. 70wt% to 95wt% aqueous sodium silicate solution;
[0037] b. 0.5 wt % to 10 wt % of the above-mentioned microporous and / or mesoporous and / or nanoporous additives;
[0038] c. Optionally, 1 wt% to 10 wt% of the above-mentioned ceramic additives imparting carbon strength;
[0039] d. Optionally, less than 10wt% of the above hardener;
[0040] e. Optionally, less than 10wt% of the above organic additives;
[0041] f. Optionally, 0.05wt% to 2wt% of the above surfactant; and
[0042] g. Optionally, 2 wt% to 10 wt% water, to reduce viscosity.
[0043] Various impregnation methods can be used, such as spraying, brushing and / or scraping. Preferably, scraping is selected for better control of thickness and feasibility of mass production. Then dry at an appropriate temperature (e.g., room temperature) to remove moisture without causing defects such as warping. The purpose of this is to make the sheet dry enough so that it can be easily peeled off from the non-stick polymer sheet. Optionally, curing can be performed at a higher temperature (e.g., 60°C) to speed up the process. Drying and / or curing can be performed by hot air, microwave heating, infrared heating, etc. The drying and / or curing temperature should not be too high, otherwise it will cause defects such as cracking and warping of the expansion sheet. Drying and / or curing conditions (e.g., temperature and duration) depend on many factors, such as the thickness of the expansion sheet to be manufactured, and even the type of oven used, and must be adjusted accordingly to obtain the best results. Optionally, the above-mentioned hardener can be added to accelerate the drying and / or curing process of the produced expansion sheet, which is particularly feasible for continuous production lines.
[0044] According to an example of the present disclosure, an expansion sheet is provided. Its composition and related properties before and after exposure to high temperature are summarized in Table 1 and Table 2, respectively. Table 1 and Table 2 are provided below. A non-woven glass fiber mat with a thickness of 0.5 mm before impregnation is used. The thickness of the expansion sheet after curing is 0.4 mm. The expansion sheet can be used as an independent sheet or stacked by assembling layer by layer, wherein the same impregnation solution (i.e., alkali metal silicate-based solution) as previously described is applied between each layer. Specifically, the assembly includes stacking a plurality of non-woven fiber mats layer by layer, and applying the impregnation solution between each layer to impregnate each layer of the non-woven fiber mat with the impregnation solution. Cold pressing is applied to multiple stacked layers to form a multilayer laminate. Independent sheets or multilayer laminates will be used as spacers in electric vehicle (EV) batteries, for example, between battery cells in EV batteries. They can be made to have the same surface area as the battery cell, or they can be made slightly larger, i.e., 2 cm to 3 cm larger around all sides of the battery cell. If a battery cell experiences thermal runaway, the adjacent expansion sheet spacer will rapidly undergo endothermic degradation and expansion as soon as the temperature reaches 200°C, forming a mechanically strong char and good thermal and dielectric isolation. This can significantly reduce heat flow and prevent high-pressure smoke and shrapnel from being transferred to adjacent battery cells, thereby preventing thermal runaway of adjacent battery cells. If the area of the expansion sheet or laminate used is slightly larger than the above-mentioned battery cell, the adjacent battery cell can be further protected from lateral thermal attack, that is, it makes it more difficult for heat to bypass the spacer laterally. Depending on the type of battery cell used, for example for prismatic battery cells, when thermal runaway occurs, the participating battery cell may dent inward. Due to the nature of the expansion sheet, when activated at higher temperatures, it softens during the expansion process and solidifies into a hard char after expansion. This allows the char to expand so as to fit closely to the shape of the dent, thereby providing enhanced thermal runaway protection for adjacent battery cells.
[0045] Table 1: Composition of expansion tablets
[0046]
[0047] Table 2: Selected properties of expansion sheets
[0048]
[0049] Some selected properties of the examples of intumescent sheets in Table 2 were obtained in the following manner.
[0050] The expansion ratio is obtained by placing each of the plurality of expansion sheets onto a hot plate preheated to 300°C for 10 minutes to form a fully expanded char through an "overlap" step. The expansion ratio range is determined by calculating the ratio between the thickness of the fully expanded char of the expansion sheet and the original thickness of the expansion sheet before expansion. The original thickness of the expansion sheet tested for determining the expansion ratio range is between 0.4 mm and 1 mm.
[0051] For thermal conductivity, the expanded sheet (or laminate) is placed in a closed fixture with spacers to expand the sheet to form a char. The closed fixture ensures a smooth surface for accurate testing of thermal conductivity. The fixture assembly is then placed on a hot plate at 300°C for 30 minutes. The size of the expanded sheet is approximately 20cm x 20cm. The obtained char is then measured using a heat flow meter (HFM) at room temperature and 50°C to obtain its thermal conductivity coefficient.
[0052] As for the compressive strength, the expanded sheet with the size of 5 cm×5 cm was placed on a hot plate at 300°C for 10 minutes through the "lap" step to ensure the formation of fully expanded char. After the char was cooled, the compressive stress-strain relationship of the char was tested by an Instron mechanical tester with a 5 kN load cell.
[0053] Regarding the above-mentioned "lapping" step, specifically, the expansion sheet is overlapped on the hot plate to ensure that the sheet is flat on the hot plate. The purpose of this is to ensure that the entire area of the expansion sheet is evenly heated, while producing a uniformly expanded char.
[0054] In one example of the present disclosure, an expansion sheet or laminate as described above may be placed in contact with (e.g., sandwiched between) a compressible material. The compressible material may be joined to the expansion sheet or laminate by layer-by-layer assembly. They are then used as spacers between battery cells in an EV battery. Compressible materials include, but are not limited to, polymer foams such as polyurethane foams and silica-aerogel foams. This provides a viable option for meeting the early life (BOL) and end of life (EOL) compressibility and thickness under compression requirements of EV battery manufacturers.
[0055] Thermal runaway (TR) comparison tests were conducted between a cell-cell spacer polyurethane foam (PUF) widely adopted by EV manufacturers and an expansion sheet-PUF combination of the same thickness. The expansion sheet combined with the PUF was similar to that described in the above example. TR testing was performed on two cell-cell spacers assembled between three prismatic cells of an EV battery, with the entire configuration compressed at 100 kPa. For the first spacer, a 1.7 mm PUF was used (1.7 mm is the thickness of the compressed PUF), and for the second spacer, a 0.5 mm expansion sheet was assembled with a 1.2 mm polyurethane foam (1.2 mm is the thickness of the compressed PUF). When thermal runaway in the first of the three prismatic cells was forced to initiate, the PUF in the first spacer quickly melted, causing the adjacent second of the three prismatic cells to undergo thermal runaway within 73 seconds. However, when the second battery cell thermally runs away, the PUF in the second spacer melts simultaneously, and the expansion sheet expands to fill the entire spacer (left by the melted PUF), thereby providing an excellent thermal insulation barrier, providing thermal protection for about 16 minutes before the adjacent third of the three prismatic battery cells thermally runs away. This test shows that the combination of compressible materials and expansion sheets or laminates can provide excellent thermal runaway protection for EV batteries.
[0056] In one example of the present disclosure, the expansion sheet or laminate described in the above example can be used as an inner wall lining of an electric vehicle (EV) module and a battery pack housing. For inner walls with complex geometries, thinner non-woven fiber mats can be used, and / or organic additives can be added to the impregnation solution to improve the flexibility of the expansion sheet or laminate used. A layer-by-layer method can be adopted to lay (i.e., laminate) individual expansion sheet layers (each layer containing a non-woven fiber mat) on the inner wall of the EV module and / or battery pack housing. The impregnation solution can be applied between the layers to act as an interlayer adhesive. In this case, there will be multiple layers of non-woven fiber mats to increase the thermal insulation and mechanical strength of the inner wall. Therefore, the inner wall and its lining will be able to accommodate high-pressure smoke and shrapnel from multiple battery cells experiencing thermal runaway. Preferably, the minimum thickness of this laminated inner wall lining is 1 mm (estimated to be about 2 expansion sheet layers), and preferably at least 2 mm (estimated to be about 4 expansion sheet layers) to give the desired performance.
[0057] In another example of the present disclosure, an expansion tape can be produced from the expansion sheet or laminate described in the above examples. An adhesive backing is attached to the expansion sheet or laminate to form the expansion tape. This allows for easy layer-by-layer assembly with other materials, such as foam, to be combined with the expansion sheet or laminate, or the expansion tape can be attached as a single layer or multiple layers to the inner wall of an EV battery or EV module or battery pack housing.
[0058] In summary, examples of the present disclosure are directed to thermal runaway management of electric vehicle (EV) batteries by using one or more thin inorganic intumescent sheets or laminates used as spacers between battery cells. Consistent with the importance of space optimization for EV battery manufacturers, the flame-retardant one or more intumescent sheets or laminates of examples of the present disclosure are able to provide the necessary thermal runaway protection at a thickness of less than or equal to 1 mm.
[0059] On the other hand, examples of the present disclosure relate to fire prevention of electric vehicles in the event that multiple battery cells in an EV battery experience thermal runaway. This is accomplished by containing the fire within the corresponding battery module and / or battery pack using the expansion sheet or laminate of examples of the present disclosure as the inner wall lining of the battery module and / or battery pack.
[0060] One or more intumescent sheets or laminates of examples of the present disclosure are made by impregnating a nonwoven fiber mat with an alkali metal silicate-based solution containing a small amount of microporous and / or mesoporous and / or nanoporous additives, which can be aerogel particles, and optionally can be a small amount of other carbon strength imparting additives, such as ceramic powders. After curing, the impregnated nonwoven fiber mat retains significant flexibility, which is critical to preventing cracks during EV battery operation (i.e., due to vibration / pressure between cells).
[0061] Under normal operating conditions, the thermal conductivity of one or more expansion sheets or laminates of examples of the present disclosure is relatively high, allowing heat diffusion to reduce the risk of any particular battery cell experiencing thermal runaway. If one battery cell in an EV battery experiences thermal runaway, an adjacent spacer including one or more expansion sheets or laminates can be activated and undergo expansion in an endothermic manner when the temperature reaches, for example, 200°C. The resulting char can be a mechanically strong inorganic char and is further supported by the impregnated non-woven fibers, which is able to resist high-pressure smoke and shrapnel. In addition, due to the presence of the microporous and / or mesoporous and / or nanoporous network, the char has a high dielectric resistance and low thermal conductivity, thereby forming an effective barrier to prevent adjacent battery cells from experiencing thermal runaway.
[0062] An example of an expansion sheet or laminate described in the above example may be referred to as a FR sheet (or "FR-sheet"). A FR-sheet refers to an expansion sheet for thermal runaway management of electric vehicle batteries. The thickness of the sheet is less than 2 mm, preferably less than or equal to 1 mm. For example, the expansion sheet is formed by impregnating non-woven inorganic fibers with an alkali metal silicate-based solution (hereinafter "impregnation solution"). The impregnation solution may be a water-based expansion coating containing aerogel. The impregnation solution may contain additives, and after it is dried and / or cured, the expansion sheet has an alkali metal silicate-based coating with additives.
[0063] The composition of the expanded sheet (after drying) and the composition of the impregnation solution of the FR sheet example are described below.
[0064] The expansion sheet may include a non-woven inorganic fiber mat (or fabric), such as Owens Corning's ECR-50 (a type of E glass). The impregnation solution for this product contains a sodium silicate-based binder and aerogel fine particles with hydrophobic surface groups. The aerogel particles have a particle size between 10 μm and 60 μm and a porosity greater than 90%. Alumina (a metal oxide) and metal dihydroxide (a metal hydroxide) are added to the impregnation solution as additives to improve the mechanical strength, insulation and flame retardancy of the char produced by the FR sheet under thermal exposure.
[0065] Tables 3 and 4 below show examples of the composition of the FR sheet after drying and the composition of the impregnation solution.
[0066] Table 3: Composition of expanded sheet (after drying)
[0067]
[0068] Table 4: Composition of the impregnation solution
[0069]
[0070] In an example, a surfactant that is stable in the pH range of 2 to 12 is added to the impregnation solution to improve the spreading and wetting ability of the nonwoven inorganic fiber mat. Preferably, the surfactant is selected from the group consisting of amine oxides, alkyl carbohydrate esters, alkoxylated polysiloxanes, and polyalkyl acrylates. The loading level of the surfactant is 0.2 wt % to 0.5 wt % of the impregnation solution, and the preferred loading level is 0.2 wt % to 1.2 wt % of the expanded sheet.
[0071] In addition to E-glass, S-glass is also a preferred choice for the nonwoven inorganic fiber mat of this example. If E-glass is used, E-glass with the boron oxide element removed is most preferred. The diameter and length of the fiber should be between 10 μm and 15 μm and 15 mm and 60 mm.
[0072] Microporous thermal insulation additives (i.e., agents capable of forming a dense network of carbon) such as fumed silica, hollow micro glass spheres may be added. Suitable carbon strength imparting ceramic additives such as metal oxides, metal hydroxides, metal carbonates, metal silicates and / or combinations of metal powders may be added.
[0073] In addition to the above ingredients, the intumescent sheet of this example may optionally contain 1 wt% to 10 wt% of a sunscreen, such as iron oxide, silicon carbide and / or titanium dioxide. The sunscreen provides high temperature insulation and is used for reflection, thereby reducing heat transfer by radiation at high temperatures.
[0074] Organic additives may be added at the impregnation station (where impregnation of the nonwoven inorganic fiber mat and the impregnation solution is performed) to enhance the flexibility and water resistance of the expanded sheet. Glycerol and polyvinyl alcohol are preferred examples of organic additives.
[0075] The production of the impregnation solution includes sequentially adding an alkali metal silicate solution and one or more surfactants, then adding a barrier imparting agent, a carbon strength imparting agent and other additives, and finally adding the necessary amount of water after each step (i.e., after each component is added sequentially) and stirring and mixing for less than 30 minutes (e.g., 15 minutes), and finally stirring and mixing the solution with all the added components for another 2 to 3 hours. The hardener is the last ingredient added to the impregnation solution and is added before impregnating the nonwoven inorganic fiber mat. The viscosity is preferably between 200 centipoise and 500 centipoise (cps).
[0076] The hardener is preferably sodium fluorosilicate or potassium methylsilicate (most preferred).
[0077] If a sunscreen, a hardener and water are added, the composition of the dipping solution is as shown in Table 5 below.
[0078] Table 5: Composition of the impregnation solution (different from the product in Table 3 above)
[0079]
[0080] Multiple intumescent sheets may be stacked together to form a laminate by applying an impregnation solution between the layers and cold pressing the multiple intumescent sheets.
[0081] In one use scenario of the product in an electric vehicle (EV) battery, the above expansion sheet or laminate is placed in contact with a polymer foam, such as polyurethane foam (PUF), which is a compressible material, which is used as a battery cell spacer. The area of the expansion sheet / laminate is preferably larger than the surface area of the battery cell to cover all sides of the battery cell by 2cm to 3cm, thereby further protecting adjacent battery cells from thermal attack on the surface.
[0082] In the event of thermal runaway in one battery cell in an EV battery, the PUF in the spacer melts simultaneously, and the expansion sheet expands to fill the entire spacer (left behind by the melted PUF), providing an excellent thermal insulation barrier to prevent thermal runaway in adjacent battery cells of the battery module.
[0083] In another use scenario of the product in an electric vehicle battery, the adhesive backing is attached to an expansion sheet or laminate as described above to form an expansion tape. This allows for easy layer-by-layer assembly with other materials, such as aerogel foam, mica sheets, etc., i.e., the expansion sheet or laminate in tape form can be adhered to these other materials to be placed in the EV battery for thermal runaway management. In addition, the expansion tape can be adhered to the inner wall of the EV battery module or EV battery pack housing in a single or multiple layers.
[0084] To produce the intumescent sheet, a nonwoven inorganic fiber mat is first laminated onto a non-stick polymer sheet and impregnated with an alkali metal silicate-based aqueous solution (ie, the impregnation solution).
[0085] Various impregnation methods can be used, such as spraying, brushing and / or scraping. Preferably, scraping is selected for better thickness control and feasibility of mass production. Drying is then performed at an appropriate temperature (e.g., room temperature) to remove moisture without causing defects such as warping. Optionally, curing can be performed at a higher temperature (e.g., by microwave heating) to speed up the process.
[0086] Other char strength enhancing additives may be added including zirconium oxide and colloidal silica. Sodium silicate is defined by the molar ratio between silica:sodium oxide. Increasing the proportion of silica enables the formation of a stronger char, and the addition of colloidal silica can adjust the increase.
[0087] Another example of the above FR-sheet may have the following characteristics:
[0088] Expansion performance:
[0089] Fast reaction at temperatures >175°C
[0090] Expand to 5 times the original thickness
[0091] Creates an insulating foam that fills voids and reduces heat transfer
[0092] Non-flammable inorganic formula
[0093] FR-sheet can be a flexible sheet material manufactured in bulk roll form for lamination and die cutting. The standard thickness of FR-sheet is 0.4mm to 1.0mm. Please refer to Table 6 below (i.e. 6(A) and 6(B)) for details.
[0094] Table 6: Typical properties of FR-sheet 6 (A) Typical properties – 0.4 mm thickness
[0095]
[0096] * Five times expansion
[0097] 6(B) Product Range
[0098]
[0099] In one example, the FR-sheet can be a square or rectangular shaped sheet, which is a suitable shape for most EV batteries.
[0100] The FR-sheet can be used alone or as a layer inserted together with one or more other layers of material (eg PUF, other thermal insulation materials, etc.).
[0101] FR-sheets are available in bulk rolls. FR-sheets can be cut to the correct size using a die-cutting process.
[0102] The FR-sheet may be supplied from more than one FR-sheet stacked on top of each other. In this case, a release liner may be provided between the layers of more than one FR sheet.
[0103] Examples of the present disclosure may have the following features.
[0104] An expansion sheet for thermal runaway management of an electric vehicle battery, wherein, out of 100 weight percent (wt%) of the expansion sheet, the expansion sheet comprises: 5 wt% to 20 wt% of a nonwoven fiber mat;
[0105] 60 wt% to 95 wt% of an alkali metal silicate-based binder; and
[0106] 0.5 wt% to 10 wt% of microporous and / or mesoporous and / or nanoporous additives,
[0107] Therein, an alkali metal silicate-based binder is impregnated into a nonwoven fiber mat by impregnating the nonwoven fiber mat with an alkali metal silicate-based solution.
[0108] The expansion sheet may have a thickness less than or equal to 1 mm.
[0109] The alkali metal silicate based binder may have a silica:alkali metal oxide molar ratio in the range of 2.5 to 4.
[0110] The alkali metal silicate based binder may have a silica:alkali metal oxide molar ratio in the range of 3 to 3.3.
[0111] The intumescent sheet may comprise 75 wt % to 85 wt % of an alkali metal silicate based binder.
[0112] The microporous and / or mesoporous and / or nanoporous additive may comprise aerogel particles having hydrophobic surface groups.
[0113] Aerogel particles can have a particle size of 10 μm to 60 μm, a pore size of 5 nm to 50 nm, a porosity of >90%, a viscosity of 0.02 g / cm3 To 0.1g / cm 3 The bulk density and 500m 2 / g to 900m 2 / g of surface area.
[0114] The microporous and / or mesoporous and / or nanoporous additive may comprise hollow microglass spheres, fumed silica and / or hollow microbeads.
[0115] The intumescent sheet may include 1 wt % to 10 wt % of a sunscreen agent, the sunscreen agent including any one of iron oxide, silicon carbide and titanium dioxide or a combination thereof.
[0116] The intumescent sheet may include 1 wt % to 10 wt % of a char strength imparting ceramic additive, the ceramic additive including any one of metal oxides, metal hydroxides, metal carbonates, metal silicates and metal powders or a combination thereof.
[0117] The intumescent sheet may comprise 3 wt % to 8 wt % of a carbon strength imparting ceramic additive.
[0118] The carbon strength imparting ceramic additives may include magnesium oxide, aluminum oxide, calcium oxide and / or zinc oxide.
[0119] The carbon strength imparting ceramic additives may include aluminum trihydrate and / or magnesium dihydroxide.
[0120] The carbon strength imparting ceramic additives may include calcium carbonate and / or zinc carbonate.
[0121] The carbon strength imparting ceramic additives may comprise mica and / or talc.
[0122] The carbon strength imparting ceramic additive may comprise a metal powder, and the metal powder comprises iron, zinc and / or aluminum.
[0123] The alkali metal silicate-based solution may include 0.05 wt % to 2 wt % of a surfactant stable in a pH range of 2 to 12 in 100 wt % of the alkali metal silicate-based solution.
[0124] The alkali metal silicate-based solution may contain 0.2 wt% to 0.5 wt% of a surfactant.
[0125] The intumescent sheet may contain less than 10 wt% of a hardener comprising sodium fluorosilicate and / or potassium dimethylsilicate.
[0126] The expandable sheet may contain less than 10 wt% of an organic additive including polyvinyl alcohol and / or glycerol.
[0127] The nonwoven fiber mat may contain E-type and / or S-type glass fibers.
[0128] The nonwoven fiber mat may comprise fibers having a diameter and a length of 8 to 18 μm and 10 to 75 mm, respectively.
[0129] The nonwoven fiber mat may comprise fibers having a diameter and a length of 10 μm to 15 μm and 15 mm to 60 mm, respectively.
[0130] The nonwoven fiber mat may include 5 wt % to 20 wt % of the acrylic resin as a binder in 100 wt % of the nonwoven fiber mat.
[0131] The nonwoven fiber mat may include 8 wt % to 15 wt % of the acrylic resin.
[0132] The nonwoven fiber mat may have a thickness of less than 400 g / m 2 area density.
[0133] The nonwoven fiber mat may have a 30 g / m 2 Up to 280g / m 2 area density.
[0134] The intumescent sheet may comprise 8 wt % to 16 wt % of the nonwoven fiber mat.
[0135] The expansion sheet can be made 2cm to 3cm larger than all sides of the battery cell of the EV battery.
[0136] Expansion sheets may include:
[0137] 8 wt % to 16 wt % of a nonwoven fiber mat;
[0138] 75 wt% to 85 wt% of an alkali metal silicate-based binder;
[0139] 1 wt % to 5 wt % of aerogel fine particles having hydrophobic surface groups; and
[0140] 3wt% to 8wt% of metal oxides and / or hydroxides.
[0141] In 100 weight percent (wt%) of the alkali metal silicate-based solution, the alkali metal silicate-based solution may include:
[0142] 92 to 97 wt % of an alkali metal silicate and water;
[0143] 0.2 wt % to 1 wt % of a surfactant;
[0144] 0.8 wt% to 2 wt% of aerogel fine particles having hydrophobic surface groups; and
[0145] 2 wt % to 4.5 wt % of metal oxides and / or hydroxides.
[0146] In 100 weight percent (wt%) of the alkali metal silicate-based solution, the alkali metal silicate-based solution may include:
[0147] 70 wt % to 95 wt % of an alkali metal silicate and water;
[0148] 0.05 wt % to 2 wt % of a surfactant;
[0149] 0.5wt% to 10wt% to obtain aerogel fine particles having hydrophobic surface groups;
[0150] 1 wt % to 10 wt % of metal oxides and / or hydroxides;
[0151] 1 wt % to 10 wt % of a sunscreen;
[0152] Less than 10 wt% of organic additives;
[0153] Less than 10 wt% of hardener;
[0154] In addition to 70 wt % to 95 wt % of alkali metal silicate and water, 2 wt % to 10 wt % of water is contained.
[0155] A method for manufacturing an expansion sheet, the method comprising:
[0156] impregnating the nonwoven fiber mat with the alkali metal silicate-based solution by coating the nonwoven fiber mat with the alkali metal silicate-based solution using a knife coating technique; and
[0157] The impregnated nonwoven fiber mat is dried.
[0158] The method may include:
[0159] Prepare the alkali metal silicate-based solution by:
[0160] a) adding an alkali metal silicate in the form of a solution;
[0161] b) adding one or more surfactants to the solution of step a) to form a mixture;
[0162] c) adding a thermal insulation imparting agent to the mixture;
[0163] d) adding a carbon strength imparting agent to the mixture;
[0164] e) adding water to the mixture;
[0165] f) adding a hardener to the mixture;
[0166] g) stirring the mixed mixture for a predetermined duration of less than 30 minutes after each of steps a) to f); and
[0167] h) After all components are added to the mixture, stir and mix for about 2 to 3 hours.
[0168] A laminate comprises a plurality of stacked layers, each of which is an intumescent sheet.
[0169] A method for manufacturing a laminate, the method comprising:
[0170] stacking a plurality of nonwoven fiber mats layer by layer and applying an alkali metal silicate-based solution between the layers to impregnate each layer of the nonwoven fiber mat with the alkali metal silicate-based solution; and
[0171] Multiple stacked layers are cold pressed to form a laminate.
[0172] The intumescent sheet and / or laminate may include an adhesive backing to facilitate adhering the intumescent sheet and / or laminate to a surface.
[0173] An electric vehicle (EV) battery includes one or more spacers located between battery cells in the EV battery to prevent thermal runaway in adjacent battery cells when one battery cell experiences thermal runaway, wherein the one or more spacers include expansion sheets and / or laminates.
[0174] One or more spacers may comprise a compressible material in contact with the expansion sheet and / or the laminate.
[0175] The expansion sheet and / or laminate may be a lining in the inner wall of a module formed from a plurality of battery cells and / or a lining in the inner wall of a battery pack housing for an EV battery.
[0176] In the specification and claims, unless the context clearly indicates otherwise, the word "comprise" has the non-exclusive meaning of "including at least", rather than the exclusive meaning of "consisting only of..." The same applies to corresponding grammatical variations of other forms of the word, such as "comprise", "comprises", etc.
[0177] Although the present invention is described in conjunction with a plurality of embodiments and implementations in this disclosure, the present invention is not limited thereto, but covers various obvious modifications and equivalent arrangements falling within the scope of the appended claims. Although features of the present invention are expressed in certain combinations in the claims, it is contemplated that these features may be arranged in any combination and order.
Claims
1. An expansion sheet for thermal runaway management of an electric vehicle (EV) battery, wherein, in 100 weight percent (wt %) of the expansion sheet, the expansion sheet comprises: 5wt% to 20wt% nonwoven fiber mat; 60 wt% to 95 wt% of an alkali metal silicate-based binder; and 0.5 wt% to 10 wt% of microporous and / or mesoporous and / or nanoporous additives, in, The alkali metal silicate-based binder is impregnated into the nonwoven fiber mat by impregnating the nonwoven fiber mat with an alkali metal silicate-based solution. 2 . The expansion sheet according to claim 1 , wherein the expansion sheet has a thickness less than or equal to 1 mm.
3. The intumescent sheet according to claim 1 or 2, wherein the alkali metal silicate-based binder has a molar ratio of silicon dioxide:alkali metal oxide in the range of 2.5 to 4.
4. An intumescent sheet according to claim 1, 2 or 3, wherein the alkali metal silicate-based binder has a molar ratio of silicon dioxide:alkali metal oxide in the range of 3 to 3.
3.
5. An intumescent sheet according to any one of the preceding claims, wherein the intumescent sheet comprises 75 to 85 wt% of an alkali metal silicate based binder.
6. An intumescent sheet according to any one of the preceding claims, wherein the microporous and / or mesoporous and / or nanoporous additive comprises aerogel particles having hydrophobic surface groups.
7. The expansion sheet according to claim 6, wherein the aerogel particles have a particle size of 10 μm to 60 μm, a pore size of 20 nm to 100 nm, a porosity of >90%, a density of 0.02 g / cm 3 To 0.1g / cm 3 The bulk density and 500m 2 / g to 900m 2 / g of surface area.
8. An intumescent sheet according to any one of the preceding claims, wherein the microporous and / or mesoporous and / or nanoporous additive comprises hollow microglass spheres, fumed silica and / or hollow microbeads.
9. An intumescent sheet according to any one of the preceding claims, wherein the intumescent sheet comprises 1 wt% to 10 wt% of a sunscreen agent comprising any one of iron oxide, silicon carbide and titanium dioxide or a combination thereof.
10. An intumescent sheet according to any one of the preceding claims, wherein the intumescent sheet comprises 1 wt% to 10 wt% of a char strength imparting ceramic additive comprising any one or a combination of metal oxides, metal hydroxides, metal carbonates, metal silicates and metal powders.
11. An intumescent sheet according to claim 10, wherein the intumescent sheet comprises 3 wt% to 8 wt% of a carbon strength imparting ceramic additive.
12. The intumescent sheet according to claim 10 or 11, wherein the carbon strength imparting ceramic additive comprises any one of magnesium oxide, aluminum oxide, calcium oxide and zinc oxide or a combination thereof.
13. An intumescent sheet according to any one of claims 10 to 12, wherein the char strength imparting ceramic additive comprises aluminium trihydrate and / or magnesium dihydroxide.
14. An intumescent sheet according to any one of claims 10 to 13, wherein the char strength imparting ceramic additive comprises calcium carbonate and / or zinc carbonate.
15. An intumescent sheet according to any one of claims 10 to 14, wherein the char strength imparting ceramic additive comprises mica and / or talc.
16. An intumescent sheet according to any one of claims 10 to 15, wherein the char strength imparting ceramic additive comprises a metal powder, and the metal powder comprises iron, zinc and / or aluminum.
17. An intumescent sheet according to any one of the preceding claims, wherein the alkali metal silicate-based solution comprises 0.05 wt% to 2 wt% of a surfactant that is stable in the pH range of 2 to 12 in 100 wt% of the alkali metal silicate-based solution.
18. The intumescent sheet according to claim 17, wherein the alkali metal silicate-based solution comprises 0.2 wt% to 0.5 wt% of the surfactant.
19. An intumescent sheet according to any one of the preceding claims, wherein the intumescent sheet comprises less than 10 wt% of a hardener comprising sodium fluorosilicate and / or potassium dimethylsilicate.
20. An intumescent sheet according to any one of the preceding claims, wherein the intumescent sheet comprises less than 10 wt% of an organic additive comprising polyvinyl alcohol and / or glycerol.
21. An intumescent sheet according to any one of the preceding claims, wherein the non-woven fiber mat comprises E-type and / or S-type glass fibers.
22. An intumescent sheet according to any one of the preceding claims, wherein the nonwoven fiber mat comprises fibers having a diameter and length of 8 to 18 μm and 10 to 75 mm, respectively.
23. The expansion sheet according to claim 22, wherein the nonwoven fiber mat comprises fibers having a diameter and a length of 10 to 15 μm and 15 to 60 mm, respectively.
24. The intumescent sheet according to any one of the preceding claims, wherein the non-woven fiber mat comprises 5 to 20 wt% of acrylic resin as a binder in 100 wt% of the non-woven fiber mat.
25. The intumescent sheet of claim 24, wherein the nonwoven fiber mat comprises 8 wt% to 15 wt% of the acrylic resin.
26. An intumescent sheet according to any one of the preceding claims, wherein the nonwoven fiber mat has a density of less than 400 g / m 2 area density.
27. An expansion sheet according to any one of the preceding claims, wherein the nonwoven fiber mat has a thickness of 30 g / m 2 Up to 280g / m 2 area density.
28. An intumescent sheet according to any one of the preceding claims, wherein the intumescent sheet comprises 8 to 16 wt% of a non-woven fibre mat.
29. An expansion sheet according to any one of the preceding claims, wherein the expansion sheet is made 2 cm to 3 cm larger than all sides of a battery cell of an EV battery.
30. An expansion sheet according to any one of the preceding claims, wherein the expansion sheet comprises: 8 wt % to 16 wt % of a nonwoven fiber mat; 75 wt% to 85 wt% of an alkali metal silicate-based binder; 1 wt % to 5 wt % of aerogel fine particles having hydrophobic surface groups; and 3wt% to 8wt% of metal oxides and / or hydroxides.
31. An intumescent sheet according to any one of the preceding claims, wherein in 100 weight percent (wt%) of the alkali metal silicate-based solution, the alkali metal silicate-based solution comprises: 92 to 97 wt % of an alkali metal silicate and water; 0.2 wt % to 1 wt % of a surfactant; 0.9 wt% to 2 wt% of aerogel fine particles having hydrophobic surface groups; and 2 wt % to 4.5 wt % of metal oxides and / or hydroxides.
32. An intumescent sheet according to any one of claims 1 to 30, wherein in 100 weight percent (wt%) of the alkali metal silicate-based solution, the alkali metal silicate-based solution comprises: 70 wt % to 95 wt % of an alkali metal silicate and water; 0.05 wt % to 2 wt % of a surfactant; 0.5 wt % to 10 wt % of aerogel fine particles having hydrophobic surface groups; 1 wt % to 10 wt % of metal oxides and / or hydroxides; 1 wt % to 10 wt % of a sunscreen; Less than 10 wt% of organic additives; Less than 10 wt% of hardener; 2 wt % to 10 wt % of water in addition to 70 wt % to 95 wt % of alkali metal silicate and water.
33. A method of manufacturing an intumescent sheet according to any one of the preceding claims, wherein the method comprises: impregnating the nonwoven fiber mat with the alkali metal silicate-based solution by coating the nonwoven fiber mat with the alkali metal silicate-based solution using a knife coating technique; and The impregnated nonwoven fiber mat is dried.
34. The method of claim 33, wherein the method comprises: Prepare the alkali metal silicate-based solution by: i) adding an alkali metal silicate in the form of a solution; j) adding one or more surfactants to the solution of step a) to form a mixture; k) adding a thermal insulation imparting agent to the mixture; 1) adding a carbon strength imparting agent to the mixture; m) adding water to the mixture; n) adding a hardener to the mixture; o) stirring the mixture for a predetermined period of less than 30 minutes after each of steps a) to f) Duration; and p) After all components are added to the mixture, stir and mix for 2 to 3 hours.
35. A laminate comprising a plurality of stacked layers, wherein each layer is an intumescent sheet according to any one of claims 1 to 32.
36. A method of making a laminate according to claim 35, wherein the method comprises: stacking a plurality of nonwoven fiber mats layer by layer and applying an alkali metal silicate-based solution between the layers to impregnate each layer of the nonwoven fiber mat with the alkali metal silicate-based solution; and Multiple stacked layers are cold pressed to form a laminate.
37. An intumescent sheet according to any one of claims 1 to 32 and a laminate according to claim 35 or 36, wherein the intumescent sheet and / or the laminate comprises an adhesive backing to facilitate affixing the intumescent sheet and / or the laminate to a surface.
38. An electric vehicle (EV) battery comprising one or more spacers located between battery cells in the EV battery to prevent thermal runaway in adjacent battery cells when one battery cell experiences thermal runaway, wherein the one or more spacers comprise an expansion sheet according to any one of claims 1 to 32 and / or a laminate according to claim 35 or 36.
39. The EV battery of claim 38, wherein the one or more spacers comprise a compressible material in contact with the expansion sheet and / or the laminate.
40. An EV battery according to claim 38 or 39, wherein the expansion sheet and / or the laminate is a lining in the inner wall of a module formed by a plurality of battery cells and / or a lining in the inner wall of a battery pack housing of an EV battery.
Citation Information
Patent Citations
A composite plate for heat dissipation and prevention of thermal runaway propagation in battery systems
CN105742755B
An all-weather effective thermal management system for lithium-ion battery packs
CN107887671B
Flame-retardant and heat-insulating elastic silica aerogel sheets and thin sheets for thermal management systems of automotive lithium-ion power batteries
CN108862286B
A method for protecting a battery cell and a battery housing a battery cell, and a protected battery cell and a protected battery housing a battery cell
JP2013528911A
Battery cooling device
JP6331017B2